A quadruple-channel fluorescent sensor array based on label-free carbon dots for sensitive detection of tetracyclines. Issue 10 (10th April 2019) - Long, Dengying; Peng, Jingdong; Peng, Huanjun; Xian, Hong; Li, Shiyu; Wang, Xiang; Chen, Jun; Zhang, Zhongying; Ni, Ranxi
Abstract : A quadruple-channel fluorescent sensor array based on label-free carbon dots (CDs) was fabricated to detect and discriminate a series of tetracyclines (TCs), including chlortetracycline (CTC), oxytetracycline (OTC), tetracycline (TC) and doxycycline (DOX). Abstract : A quadruple-channel fluorescent sensor array based on label-free carbon dots (CDs) was fabricated to detect and discriminate a series of tetracyclines (TCs), including chlortetracycline (CTC), oxytetracycline (OTC), tetracycline (TC) and doxycycline (DOX). Blue-emitting carbon dots (B-CDs) and green-emitting carbon dots (G-CDs) were prepared to serve as four sensing elements. When the TCs were directly mixed with CDs, the fluorescence quenching phenomenon appeared. Since different TCs exhibited different affinities for sensing elements, the sensor array displays a distinct fluorescence pattern of the fluorescence intensity variation ( F 0 − F)/ F 0 for each of these TCs, which is further analyzed by principal component analysis (PCA). The present fluorescent sensor array has the capacity to differentiate TCs at a low concentration of 1 μM. Meanwhile, quantitative detection with a lower limit (0.30 μM) for TCs could be achieved by applying a single element. Moreover, a high accuracy (100%) examination of unknown samples is acquired. Finally, the fluorescent sensor array performs well in distinguishing binary mixtures and could also recognize TCs in milk.